Структура и оценка состояния древесных пород буковых лесов Дагестана - Kh. U. Aliev; Z. I. Soltanmuradova; K. I. Akhmedova (Юг России: экология, развитие, 2021)
Aim. To identify the structural features and assess the current condition of woody species in the beech forests of Dagestan, Russia.Material and Methods. Research was based on the analysis of data from 69 sampling areas located in various physical-geographical regions of Dagestan. A detailed accounting of individual specimens of all age groups of each species was undertaken in the sampling areas. The total area surveyed was 43,125 m2. In total, 11,446 individuals of different species were involved in the statistical analysis, of which 1,974 form a tree tier, in which each individual is evaluated according to a scale of condition categories.Results. A study of the structure of beech forests showed the participation rate of Fagus orientalis Lipsky to be from 7.5 to 8.5 points. The average age of the upper sub-level of beech in the foothills was 110 years and in the highlands 160 years. For most woody species the age spectrum was sinistral and incomplete. Beech with a full-membered age spectrum were observed in the beech forests of the southwestern sub-region and in the high mountain region. A general trend is observed of deterioration of the condition of individuals in the transition from the upper to the lower sub-level. The average condition of beech individuals within the tree tier is 1.4 points. The condition categories of other species are characterized as being generally closer to 'weakened'.Conclusion. The results obtained regarding the structure and condition of woody species in the beech forests of Dagestan confirm the highly edifying role of beech. The greatest negative impact is exerted by the anthropogenic factor, which is confirmed by the incompleteness of the beech age spectrum and the low participation rate of the old-growth generative group and of the post-generative period.